The Effects of Saudization on the Universities: Localization in Saudi Arabia - Ahmed, Manail Anis (International Higher Education, 2016)
19.5 million Saudis out of a total population of approximately 30 million are under the age of 35. Saudi Arabia is intent on localizing its workforce and providing gainful employment to these young citizens. As with all sectors, replacing foreign workers with Saudi nationals has affected the higher education industry also. This piece briefly examines the immediate implications of employment nationalization on the performance of universities, the production of research output, and most importantly the education of students in Saudi institutions. It suggests some modifications in the implementation of Saudization in the higher education landscape of the country.